2014
DOI: 10.11648/j.jctr.20140205.12
|View full text |Cite
|
Sign up to set email alerts
|

Striking Regression of Temporal Lobe Necrosis Following Radiotherapy for Nasopharyngeal Carcinoma in a Clinical trial of Anti-Mycobacterium Therapy

Abstract: Abstract:The mechanism of radiation-induced delayed brain injuries remains poorly understood, and few treatment options are available. The aim of this study was to investigate whether temporal lobe necrosis can be reversed by anti-mycobacterium therapy (AMT). We conducted this prospective, controlled study in southern China. Ten patients with symptomatic delayed radiation injury were monitored during AMT and compared with a control group of 11 patients who received current standard therapies. Activities of dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Drugs including pembrolizumab, oxaliplatin, methylprednisolone, hydrogen peroxide, and amikacin, have been used in the clinical treatment of NPC. [44–48] These results showed that these genes might be used as promising targets for NPC therapy or metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Drugs including pembrolizumab, oxaliplatin, methylprednisolone, hydrogen peroxide, and amikacin, have been used in the clinical treatment of NPC. [44–48] These results showed that these genes might be used as promising targets for NPC therapy or metastasis.…”
Section: Discussionmentioning
confidence: 98%